- - علی ابراهیمی کردلر; الهام حسنی اذر داریانی (بررسی‌های حسابداری و حسابرسی, 2006)
This study is first research of earnings management by initial public offering (IPO) firms in Iran country. Using a sample of 30 Iranian IPO’s through 1378-1380, we investigate the pattern of discretionary current accruals (DCA) over time. We find that managers manage their company’s earnings in the first year as a public company but not in the years before the IPO. We also examine the impact of earnings management on the long-run stock price performance of IPO’s. We find a positive relation between the size of the DCA in the first year as a public company and long-run stock price performance over the next 3 years. A number of additional tests support these findings.